The psychological correlates of endowment effect: Individualism-collectivism, perspective taking, and real and hypothetical endowment effects - Gezgin, Ulaş Başar. (Thesis (M.A.) - Bogazici University. Institute of Social Science, 2002., 2002)
In this study conducted in Boğaziçi University with 121 participants, the psychological correlates of the endowment effect are probed. The endowment effect is the asymmetry between the amount that a given individual would like to pay for a certain good and the amount that this individual would like to accept to sell the same good. There are two types of endowment effect: The real endowment effect is the one observed in real or simulated economies, while the hypothetical endowment effect is the one exhibited for imaginary situations.Individualism-Collectivism and perspective taking are considered as psychological correlates of the endowment effect in this study. The study shows that there is at least some relationship between the real endowment effect and perspective taking and that individualism-collectivism is significantly correlated with perspective taking.
Keywords: Individualism -- Psychological aspects.; Collectivism -- Psychological aspects.